Pembinaan Alat Ukur Amalan Keibubapaan Muslim: Development of Measuring Muslim Parenting Practice - Jalal, Fauziah Hanim; Noor, Zanariah; Twahir @ H.Tahir, Wahibah (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2014)
<span style="display: inline !important; float: none; background-color: transparent; color: #000000; font-family: 'Helvetica Neue',Helvetica,Arial,sans-serif; font-size: 12px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 13.2px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">This study aims to describe the development of Muslim parenting practices selfreport, and report the validity and reliability. The method uses literatures from various sources of Islamic parenting and family to develop the concept and items for parenting practices. Three processes involve in developing self-report which consist of definition of concept, choosing the measurement for the concept, and empirical studies. Two constructs were named; early practices and specific practices. The early practices have 11 items that includes three sub constructs: before, current, and after born. Specific practices have 59 items with eight sub constructs are referring to educating the aspect of aqidah, worship, social, akhlaq, emotion, intellectual, physical/health and sexuality. All items in the scales were written according to several ways children were raised that include guidance and advising, role model, supervision/observation, and routines. Self-reports were administered to 372 parents selected from urban and rural area in a state. Finding shows that all the arbiters have evaluated all item that were categorized in the sub construct, and all the positive items were true and all the negative items were wrong. All the items have 79.9% agreed and both sub constructs were accepted. Item analysis show self-report items of the standardized item alpha have greater value than the alpha if item deleted for every sub contracts. All the items in the instrument are homogeneous and indirectly show construct validity. The selfreport can be used to identify the practice of parenting among parents that are in linewith religion.